2019
DOI: 10.3390/nu11112640
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Human Milk Oligosaccharides in Cord Blood and Maternal-to-Fetal Transport across the Placenta

Abstract: Human milk oligosaccharides (HMOs) are present in maternal serum in early gestation, raising the question of whether HMOs can cross the placental barrier and reach fetal circulation. Here, we aimed to detect HMOs in cord blood, and assess HMO composition and concentration in relation to maternal HMOs. In an ex-vivo placental perfusion model, we asked whether HMOs can pass over the placenta. Using HPLC, we measured HMOs in maternal serum and matching venous cord blood samples collected at delivery from normal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
2
21
0
2
Order By: Relevance
“…HMOs are pools of complex carbohydrates, the third most abundant component of human milk, and one example of naturally occurring ‘prebiotics’ [ 19 ]. Although originally characterised as HMOs, they are also present in the amniotic fluid, and thus the foetus is already exposed to HMOs prior to birth when ingesting the amniotic fluid [ 20 , 21 , 22 , 23 ].…”
Section: Oligosaccharides Bacteria and Microbial Metabolites In mentioning
confidence: 99%
“…HMOs are pools of complex carbohydrates, the third most abundant component of human milk, and one example of naturally occurring ‘prebiotics’ [ 19 ]. Although originally characterised as HMOs, they are also present in the amniotic fluid, and thus the foetus is already exposed to HMOs prior to birth when ingesting the amniotic fluid [ 20 , 21 , 22 , 23 ].…”
Section: Oligosaccharides Bacteria and Microbial Metabolites In mentioning
confidence: 99%
“…Human milk oligosaccharides already circulate in the blood of pregnant mothers at least from week 10 on [ 56 ], reaching the fetus through the amniotic fluid [ 57 ] and likely through the umbilical cord passing the placenta [ 58 ].…”
Section: Hmos Shaping the Neonatementioning
confidence: 99%
“…Additionally, it is speculated that maternal body composition affects the oligosaccharide profile during pregnancy [170]. Moreover, the level and profile of individual HMOs is similar for maternal and cord blood, which confirms the placental transport of oligosaccharides from mother to fetus [171]. Among individual oligosaccharides, the strongest relationship in concentration was observed for two fucosylated oligosaccharides, namely for 2 -FL and LDFT.…”
Section: Fucosylated Hmos Are Present Not Only In Human Milkmentioning
confidence: 70%
“…Among individual oligosaccharides, the strongest relationship in concentration was observed for two fucosylated oligosaccharides, namely for 2 -FL and LDFT. Using an ex vivo placental perfusion model, it was shown that 22% of maternal 2 -FL reached the fetal circulation, but without achieving a balance [171].…”
Section: Fucosylated Hmos Are Present Not Only In Human Milkmentioning
confidence: 99%